A técnica da linearização equivalente no cálculo da resposta permanente de plataformas marítimas fixas - Ayabe, Celso (1983)
The purpose of this work is to present the equivalent linearization technique as well as to analyse such approximation in order to obtain the steady state response of fixed offshore platforms under cyclic loads. The linearization is applied to local non linearity arising from hysteretic soil structure interation in such a manner that the non linear dynamic system is replaced by an equivalent linear one. Therefore the steady state response of the structure can be determined from a frequency domain analysis. The technique feasibility is investigated by means of some numerical soil structure interaction problems and comparisons between the approximate solution and non linear time domain solution are presented.